Focused microarray comparative genomic hybridisation compared to g-band karyotyping in a prospective prenatal population with a structural malformation identified on ultrasound scan. (7th June 2011) - Hillman, S C; McMullan, D J; Togneri, F; Hall, G; Cooper-Charles, L; Davison, V E; Williams, D; Maher, R; Kilby, M D
Abstract : Background: Array comparative genomic hybridisation (aCGH) technology has allowed examination of the human genome at previously unthinkable resolution. It has enabled the detection of microdeletions and microduplications too small to be noted on standard G-band Karyotype. Its use in the prenatal setting is appropriate due to its ability to analyse DNA from uncultured cells, its rapid turn-around of results and its ability for high throughput analysis. Its use has been approached with caution due to difficulties in interpreting copy number variance (CNVs) of unknown clinical significance which may give parents' elevated anxiety. Methods: We are prospectively recruiting a cohort of patients with structural anomalies found on ultrasound scan at FMC, Birmingham Women's hospital, UK. Patients were offered and consented to a targeted array (BlueGnome constitutional array) analysis of the fetal genome in addition to a rapid QF-PCR and G-band karyotyping. Results: Between November 2009 and October 2010, 102 cases were included; the major fetal anomalies being 28% cardiac, 22% central nervous system and 21% NT (>3.5 mm) anomalies. From the 102 cases, QF-PCR detected 19 trisomies on 81 samples to date (detection rate of 8.1%). In three (3.7%) of these samples the karyotypic anomaly was not detected by standard karyotyping. The % of pathological and benign CNVs are discussed. aCGH results were turned around 1.76 days quicker than karyotyping. Conclusions: Our ongoing prospective study has demonstrated that focused array CGH is capable of detecting chromosomal differences over PCR and G-band techniques. The impact upon prenatal diagnosis and counselling will be discussed.